Accionar de enfermería en el cuidado domiciliario a pacientes con Parkinson. - Mata Inca, Paola Jazmín (2024)
The present research, whose topic is "Nursing action in home care for patients with Parkinson's,” considers the disease a degenerative disorder that affects the central nervous system, especially the neurons that produce dopamine, with a higher frequency in men. That exceeds the age of 65 years in the initial stage are mild ailments that, as the disease progresses, the symptoms have a greater prevalence in motor and non-motor symptoms. The present study is developed under a bibliographic review in the descriptive field, analyzing 40 scientific articles from different bibliographic sources, including books, magazines, websites, blogs, and articles of academic and scientific relevance, which responds to the main objective of determining the actions of care. nursing to patients with PD using techniques and tools. Nursing actions begin with the nurse-patient dialogue. In the early stages of the disease, the treatment of the treating physician and the patient's current condition are assessed, and with the inputs and needs of the patient, actions are implemented that are socialized to the patient and family. especially in self-care, medication intake, diet, and physical activity, without neglecting the emotional state. Dorothea Orem's theory allows us to identify the self-care deficiencies that patients present. As the disease progresses, motor strength declines, causing falls and consequently a loss of autonomy. Problems such as depression and anxiety inhibit patients' activities. In daily activities such as feeding, washing, and even sleeping, home nursing care focuses on evaluating the progress of the disease and establishing actions through dialogue and prior consent that improve the quality of life of patients.